Media aesthetic environment of image formation - Zagidullina, Marina (Przegląd Wschodnioeuropejski, 2020)
This paper is devoted to the “nature of image” in the new media environment. The author re-conceptualizes the image as a basis of textual, visual and audial culture. Two factors of this revision are explained: (1) the facilitation of the complex creation and consumption of communicative unities, or artifacts (complexes of video, audio, texts and other forms), (2) the ability to capture a massive interest for new forms of imagery in social networks and the internet (a research evidence of this interest). The theory of the image, presented in the writings of Jean-Luc Nancy, is applied to the actual facts of communicative exchange allowing to identify some new directions for the development of media aesthetic phenomena. The main empirical material of the article is the growing mass interest in video and audio clips, such as #oddlysatisfying and ASMR. The author uses this material to confirm Nancy’s idea on the concentration of image formation in an “invisible” zone (beyond the representation of the object itself: the image is interlined, it is between sounds, it is behind pictures).